Contractor's support of U.S. operations in Iraq - Frisk, Daniel; Trunkey, R. Derek, 1966-; United States. Congressional Budget Office ([Washington, DC] : Congress of the United States, Congressional Budget Office, 2008)
"Contractors play a substantial role in supporting the United States' current military, reconstruction, and diplomatic operations in Iraq. That support has raised questions regarding the costs, quantities, functions, and legal status of contractor personnel working in the Iraq theater. This Congressional Budget Office (CBO) paper, which was prepared at the request of the Senate Committee on the Budget, examines the use of contractors in the Iraq theater from 2003 through 2007. It provides an overview of the federal government's costs of employing contractors in Iraq and in nearby countries, the type of products and services they provide, the number of personnel working on those contracts, comparisons of past and present use of contractors during U.S. military operations, and the use of contractors to provide security. CBO also investigated the command-and-control structure between the U.S. government and contract employees and the legal issues surrounding contractor personnel working in Iraq."--Preface.
System requirements: Adobe Reader.
Mode of access: Internet from the CBO web site. Address as of 9/04/2008: http://www.cbo.gov/ftpdocs/96xx/doc9688/08-12-IraqContractors.pdf ; current access available via PURL.
Title from caption (viewed Sept. 4, 2008).
"August 2008."
"Pub. No. 3053."
"This paper was prepared by Daniel Frisk and R. Derek Trunkey of CBO's National Security Division under the supervision of J. Michael Gilmore and Matthew Goldberg."--Preface.
Keywords: Contractors -- Government policy -- United States; Contractors -- Iraq -- Costs; Contractors -- United States -- Costs; Contractors -- Legal status, laws, etc. -- United States; Defense contracts -- United States -- Costs; Defense contracts -- Iraq -- Costs; Diplomatic and consular service, American -- Iraq; Diplomatic and consular service, American -- Appropriations and expenditures; Iraq War, 2003-2011 -- Costs; Iraq War, 2003-2011 -- Economic aspects; Postwar reconstruction -- Iraq; contractors -- Iraq -- personnel -- theater -- CBO -- 'Iraq theater' -- 'contractor personnel' -- obligations